Stimulated transformation of soft helix among helicoidal, heliconical, and their inverse helices - Yuan, Cong-long (Sci Adv, 2019)
Dynamic modulation of soft helix in terms of the molecular organization, handedness, and pitch length could result in a sophisticated control over its functions, opening numerous possibilities toward the exploration of previously unidentified applications. Here, we report a dynamic and reversible transformation of a soft helical superstructure among the helicoidal (molecules orthogonal to helical axis), heliconical (molecules oblique to the helical axis, i.e., oblique helicoidal), and their inverse helices, together with a tunability on the helical pitch, by combining electrical and optical manipulations. This multistate transformation depends on a matching of the temperature, the strength of external stimuli, and the bend and twist elastic effects of the system. A laser emission with tunable wavelength and polarization, and prescribed micropatterns formed by any aforementioned architectures were achieved.